Environmental and social drivers of urban garden biodiversity: a PRISMA-ScR review - Park, Jiwon; Jin, Hyeyoung; Jeong, Miae (Frontiers in Horticulture, 2026)
IntroductionUrban gardens are increasingly recognized as multifunctional green spaces that support biodiversity and contribute to sustainable urban living. This scoping review explores how environmental and social factors interact to shape biodiversity outcomes in urban gardens across different taxa.MethodsFollowing PRISMA-ScR guidelines, we screened an initial pool of 11,900 records retrieved from Web of Science, Scopus, and PubMed. We synthesized findings from 30 peer-reviewed studies published since 2000, including 26 core studies identified through the PRISMA-ScR process and four additional studies from a supplementary update search. For each study, we extracted taxonomic focus, garden types, spatial scales, and environmental and social variables tested as biodiversity drivers, and synthesized patterns across taxa.ResultsMost studies were conducted in Europe and North America and focused on plants and invertebrates in private and community gardens. Environmental variables—such as garden size, plant species richness, vegetation structure, and landscape connectivity—were consistently associated with higher species richness and abundance. Social and cultural factors, including gardeners’ motivations, management intensity, cultural background, and socio-economic context, shaped garden management and species assemblages. DiscussionThis review shows that urban garden biodiversity is jointly shaped by environmental heterogeneity and the decisions of diverse gardeners, but evidence remains geographically biased and taxonomically narrow. Future research should adopt more integrative socio-ecological designs, include underrepresented regions and taxa, and use more comparable biodiversity metrics. Policy and planning should recognize gardens as key components of urban green infrastructure and support management practices that enhance both ecological and social benefits.